Evaluating faculty and trainee perceptions on entrustable professional activities in dental postgraduate training: a cross-sectional survey - Asma Muhammad Yousuf; Afeefa Abul Barakaat; Kanza Tahir; Rashna Hoshang Sukhia; Mubassar Fida (BMC Medical Education)
Abstract Background Entrustable Professional Activities are essential, observable tasks that postgraduate trainees can perform independently upon demonstrating competence. EPAs provide a structured framework for competency-based education, bridging theoretical knowledge and practical application. This study aimed to evaluate the perceptions, awareness, and challenges of EPA implementation among faculty and trainees in postgraduate dental programs. Methods A cross-sectional survey was conducted among 100 faculty members and 300 trainees from various dental institutions. Structured questionnaires assessed demographic data, awareness, usage, and satisfaction with EPAs. Data were analyzed using SPSS version 26, employing Chi-square test to evaluate relationships, with a significant threshold of p < 0.05. Results A majority of faculty (63%) emphasized the necessity of prior training for effective EPA implementation, while 39% reported logistical challenges. Only 28% strongly agreed that sufficient institutional support was available. Among trainees, 34% strongly agreed on the importance of EPAs for competency development, and 50.7% expressed satisfaction with their integration. However, 35% reported performance anxiety under observation. Thematic analysis revealed variability in feedback adequacy and stress associated with direct supervision. Conclusions EPAs hold significant potential for improving CBE in postgraduate dental education. Effective implementation requires addressing resource constraints, enhancing faculty training, and fostering supportive environments for trainees. Institutional alignment with curricular goals and systematic feedback mechanisms are critical for success. Integrating EPAs into postgraduate dental curricula can enhance training outcomes by providing a structured approach to competency assessment. Addressing implementation barriers will ensure post-graduates are prepared for independent clinical practice.